An Explanatory Model of Violent Behavior, Self-Concept, and Alcohol, Tobacco, and Cannabis Consumption in Secondary Education Students. (15th April 2023) - Melguizo-Ibáñez, Eduardo; González-Valero, Gabriel; Badicu, Georgian; Clemente, Filipe Manuel; Silva, Ana Filipa; Puertas-Molero, Pilar
Abstract : Background . Current scientific evidence establishes that regular physical activity engagement provides numerous physical and mental benefits. Thus, the present research aims at examining the relationships between violent behavior, self-concept, and consumption of alcohol, tobacco, and cannabis. Specifically, two objectives were defined: (a) analyze and establish the relationships between violent behaviors, the different dimensions of self-concept, and the consumption of alcohol, tobacco, and cannabis as a function of physical activity engagement, (b) define and examine a proposed explanatory model, and (c) analyze the effect of self-concept on alcohol and tobacco consumption and physical activity engagement based on the explanatory model developed. Methods . For this purpose, a nonexperimental (ex post facto), descriptive, and cross-sectional study was conducted. For data collection, a sociodemographic questionnaire was administered alongside the Self-Concept Form 5 and the School Victimization Scale. Results . It was shown that individuals engaging in more than three hours of physical exercise per week scored more highly on the social, family, physical, and emotional aspects of self-concept, whilst those who do not meet this criterion scored more highly on the academic aspect and on physical and verbal victimization. Conclusions . The present research concludes that engagement in more than 3 hours of physical activity per week led to benefits in a number of domains of self-concept whilst, at the same time, increasing levels of violence.